Effect of the antioxidant idebenone on maternal diabetes-induced embryo alterations during early organogenesis - Higa, Romina Daniela (2018)
Research question: Can maternal treatments with idebenone, a structural analogue of coenzyme Q10, prevent alterations on markers of proinflammatory–prooxidant processes, on the expression of genes involved in mitochondrial biogenesis and function, and on the apoptotic rate in embryos from mild diabetic rats? Design: A mild diabetic rat model was induced by neonatal–streptozotocin administration (90 mg/kg subcutaneously). Female diabetic rats and controls were mated with healthy males. From day 1 of pregnancy, control and diabetic rats were orally treated with idebenone (100 mg/kg daily). On day 10.5 of gestation, the embryos were explanted and prepared for immunohistochemical studies, for the evaluation of gene expression by reverse transcription polymerase chain reaction and for TdT (terminal deoxynucleotidyl transferase)-mediated dUDP nick-end-labelling assay analysis. Results: Embryos from mild diabetic rats showed increased levels of nitrated proteins, 4-hydroxynonenal and matrix metalloproteinase 9, which were prevented by idebenone administration. We also found a decreased embryonic expression of cytochrome c oxidase and reduced mRNA levels of peroxisome proliferator activated receptor-γ coactivator-1-α and nuclear respiratory factor-1, both of which were prevented by idebenone administration to the diabetic pregnant rats. Embryos from mild diabetic rats also showed an increased apoptotic rate, which was diminished by idebenone treatment. Conclusion: Maternal idebenone treatment ameliorates altered parameters related to the prooxidant–proinflammatory environment found in embryos from mild diabetic rats, suggesting a putative treatment to prevent diabetes-induced embryo alterations.